2017
DOI: 10.1111/nana.12347
|View full text |Cite
|
Sign up to set email alerts
|

Language as a public good and national identity: Scotland's competing heritage languages

Abstract: The preservation of one or several historically and culturally important languages may be a salient political issue in some polities. Although they may not be used as an active means of communication, these languages can also serve a symbolic identitary function. These ‘heritage’ languages can be seen as ‘public goods’ and that even non‐speakers of these languages can have opinions regarding their importance to national identity. In the Scotland example, while Gaelic has been the focus of proactive government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…I put forward this argument in an attempt to understand the nature of inconsistencies we found between parental attitudes and actual practices. In this way, it becomes obvious that our finding provides support for Chhim and Bélanger's (2017) premise stating that with the absence of proficiency in a given language, people can still have opinion about its status as well as enjoy a sense of belonging to it. Furthermore, their study discovered that people's perception and belief toward Welsh and Irish in particular are not constrained with their ability and motivation to learn it.…”
Section: Attitudes On the Use Of Javanese As Home Languagesupporting
confidence: 73%
“…I put forward this argument in an attempt to understand the nature of inconsistencies we found between parental attitudes and actual practices. In this way, it becomes obvious that our finding provides support for Chhim and Bélanger's (2017) premise stating that with the absence of proficiency in a given language, people can still have opinion about its status as well as enjoy a sense of belonging to it. Furthermore, their study discovered that people's perception and belief toward Welsh and Irish in particular are not constrained with their ability and motivation to learn it.…”
Section: Attitudes On the Use Of Javanese As Home Languagesupporting
confidence: 73%
“…The present study thus shows the broader attitudinal effects of exposure to Gaelic road and public signage to be more complex than rhetoric advocating the increased national visibility of Gaelic on signage assumes (Bòrd na Gàidhlig, 2007Gàidhlig, , 2012MacIlleathain, 2011;Chhim & Bélanger, 2017: see Section 1).The sociolinguistic context of Gaelic in Scotland may contribute to such findings. As we noted earlier, Scottish Gaelic is spoken by only 1.1% of the Scottish population, with the most densely Gaelic-speaking areas existing in the Highlands and Islands, in the North-West of the country.…”
Section: Discussionmentioning
confidence: 62%
“…Several recent surveys of the Scottish population have found that a large proportion of Scotsfar larger than the 1.1 % who speak the language, or indeed the rather larger proportion with a recent family history of Gaelic speakingsee Gaelic as an important element in Scottish culture, heritage or identity (West and Graham 2011;Paterson and O'Hanlon et al 2013;Paterson and O'Hanlon 2015;Chhim and Éric 2017). Results vary substantially, of course, according to the precise question asked.…”
Section: Gaelic As a National Languagementioning
confidence: 99%